2016
DOI: 10.1530/rep-16-0313
|View full text |Cite
|
Sign up to set email alerts
|

A role for seminal plasma in modulating pregnancy outcomes in domestic species

Abstract: Seminal plasma is a complex fluid produced by the accessory glands of the male reproductive tract. Seminal plasma acts primarily as a transport medium for sperm on its arduous journey through the male and then female reproductive tract following ejaculation. This spermatozoan expedition will hopefully result in the meeting of and resultant fertilization of an oocyte, perpetuating the genetic lineage of both sexes. Whereas seminal plasma has historically been perceived as only a transport medium providing a nut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
85
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 83 publications
1
85
0
1
Order By: Relevance
“…Despite less documented than in the testis and excurrent ducts, AQPs are also present in accessory glands, which are crucial for their contribution to seminal plasma (see Bromfield, for review). In effect, AQP1 is found in the prostate and seminal vesicles (Brown et al., ) and AQP9 is found in the prostate and the coagulating gland of rats (Pastor‐Soler et al., ).…”
Section: Aquaporins In the Male Reproductive Tractmentioning
confidence: 99%
“…Despite less documented than in the testis and excurrent ducts, AQPs are also present in accessory glands, which are crucial for their contribution to seminal plasma (see Bromfield, for review). In effect, AQP1 is found in the prostate and seminal vesicles (Brown et al., ) and AQP9 is found in the prostate and the coagulating gland of rats (Pastor‐Soler et al., ).…”
Section: Aquaporins In the Male Reproductive Tractmentioning
confidence: 99%
“…However, in artificial insemination, semen can be deposited at the anterior os of the cervix, just inside the uterus or using a deep‐uterine technique (Bergeron, Crête, Brindle, & Manjunath, ). Thus varying amounts of SP can enter the uterus, as it is not removed during processing—it is merely diluted by adding semen extender (Bromfield, ). The proportion of bovine SP included in frozen semen depends on the sperm concentration, the intended number of sperm per straw and possibly on the predicted fertility of the bull.…”
Section: Discussionmentioning
confidence: 99%
“…A rough estimation of the amount of seminal plasma normally found in a bull semen dose can be obtained by assuming that the spermatozoa occupy a volume of 1.0–1.5 ml in raw semen (depending on the sperm concentration). Using this rough estimation, we found that commercial semen doses contain approximately 0.8%–12% SP (Bromfield, ; Hering, Oleński, Ruść, & Kaminski, ). The proportions of SP investigated here (75 μl and 300 μl) represent 1% and 4% of the cell culture medium; it is difficult to obtain a higher proportion in our cell culture system without depriving the cells of nutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations